Derry City : memory and political struggle in Northern Ireland - Shea, Margo, 1970- (University of Notre Dame Press, 2020)
"Derry is the second largest city in Northern Ireland and has had a Catholic majority since 1850. It was witness to some of the most important events of the civil rights movement and the Troubles. This study examines Catholic Derry from the turn of the twentieth century to the end of the 1960s and the start of the Troubles. Plotting the relationships between community memory and historic change, Margo Shea provides a rich and nuanced account of the cultural, political, and social history of Derry using archival research, oral histories, landscape analysis, and public speeches. Looking through the lens of the memories Catholics cultivated and nurtured as well as the memories they contested, she illuminates Derry's Catholics' understandings of themselves and their Irish cultural and political identities through the decades that saw Home Rule, Partition, and four significant political redistricting schemes designed to maintain unionist political majorities in the largely Catholic and nationalist city. Shea weaves local history sources, community folklore, and political discourse together to demonstrate how communities maintain their agency in the midst of political and cultural conflict. As a result, the book invites a reconsideration of the genesis of the Troubles and reframes discussions of the "problem" of Irish memory. It will be of interest to students and scholars of memory, modern and contemporary British and Irish history, public history, the history of colonization, and popular cultural history"--